Effects of atmospheric Ti (III) reduction on Nb2O5-doped Li4Ti5O12 anode materials for lithium ion batteries - Kim, Seul-Ki; Kwon, Eun-Seok; Kim, Tae-Heui; Moon, Jooho; Kim, Joosun (ELSEVIER SCI LTD, 2014)
The effects of atmospheric annealing on electrochemical performance for Nb2O5-doped Li4Ti5O12 anode materials have been investigated. The annealing of Nb2O5-doped Li4Ti5O12 in Ar-gas suppressed the capacity fade, under the condition of a high charge discharge rate, by virtue of an enhanced exchange reaction at the electrode/electrolyte interface. Under Ar-gas, Nb2O5-doped Li4Ti5O12 was primarily reduced to increase the density of Ti3+ ions. This caused expansion of the Li4Ti5O12 lattice, but had little impact on Li-ion diffusion into the lattice. When concurrent doping and annealing induced such compositional and electrical modification of Li4Ti5O12, the polarization resistance of exchange reactions at the electrode/electrolyte interface decreased. Therefore, we have demonstrated that annealing in Ar-gas is capable of decreasing the resistance of exchange reactions at the electrode/electrolyte interface. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: HIGH-RATE PERFORMANCE; ELECTROCHEMICAL PROPERTIES; ELECTRICAL-CONDUCTIVITY; RATE-CAPABILITY; SPINEL; COMPOSITE; STORAGE; CARBON